Rethinking political Islam - Hamid, Shadi; McCants, William Faizi (Oxford University Press, 2017)
Egypt / by Steven Brooke -- Tunisia / by Monia Marks -- Morocco / by Avi Spiegel -- Syria / by Raphaël Lefèvre -- Yemen / by Stacey Philbrick Yadav -- Libya / by Omar Ashour -- Saudi Arabia / by Toby Matthiesen -- Kuwait / by Courtney Freer -- Jordan / by David Patel -- Pakistan / by Matthew Nelson -- Southeast Asia / by Joseph Chinyong Liow -- Islamism and U.S. foreign policy / by Peter Mandaville -- Amr Darrag, Egyptian Muslim Brotherhood leader, in conversation with Steven Brooke -- Sayida Ounissi, Ennahda member of the Tunisian Parliament, in conversation with Monica Marks -- Ammar Fayed, Muslim Brotherhood youth activist on the state of the Brotherhood today -- "How much do organizational structures matter?" / Jacob Olidort in conversation with Raphaël Lefèvre -- "The relationship between religious literacy and religious motivation" / by Andrew Lebovich -- "Does islamism have an intellectual deficit?" / by Ovamir Anjum